(untitled) (Transport systems and technologies, 2022)
The paper deals with the properties of the Fast Kurtogram technique for the vibrodiagnostics of rolling bearings of electric motor. Taking into account the disadvantages of the classic tools of vibrodiagnostics in the time domain, the proper frequency band selection procedure was suggested for the further demodulation and envelope spectrum extraction. Fast Kurtogram represents the spectral kurtosis value of the signal on the (f, f) plane. The frequency and the frequency resolution are used as the key functions to determine the magnitude of the spectral kurtosis. The best combination makes the kurtosis maximum. During the experimental research the vibration of the rolling bearing of electric motor of electric locomotive ChS7 series was acquired. The broadband spectrum in the frequency range 0 – 9 kHz was extracted and with the help of empiric approach the four frequency bands with resonance excitations were selected. None of four envelope spectra did not have any informative features among numerous random components. After the selection of a proper center frequency and the frequency band by the Fast Kurtogram, the extracted envelope spectrum has shown the series of harmonics related to the outer race faults.